Demonstration of the first‐pass metabolism in the skin of the hair dye, 4‐amino‐2‐hydroxytoluene, using the Chip2 skin–liver microphysiological model. Issue 10 (17th February 2021) - Tao, Thi Phuong; Brandmair, Katrin; Gerlach, Silke; Przibilla, Julia; Géniès, Camille; Jacques‐Jamin, Carine; Schepky, Andreas; Marx, Uwe; Hewitt, Nicola J.; Maschmeyer, Ilka; Kühnl, Jochen
Abstract: We used TissUse's HUMIMIC Chip2 microfluidic model, incorporating reconstructed skin models and liver spheroids, to investigate the impact of consumer‐relevant application scenarios on the metabolic fate of the hair dye, 4‐amino‐2‐hydroxytoluene (AHT). After a single topical or systemic application of AHT to Chip2 models, medium was analysed for parent and metabolites over 5 days. The metabolic profile of a high dose (resulting in a circuit concentration of 100 μM based on 100% bioavailability) of AHT was the same after systemic and topical application to 96‐well EpiDerm™ models. Additional experiments indicated that metabolic capacity of EpiDerm™ models were saturated at this dose. At 2.5 μM, concentrations of AHT and several of its metabolites differed between application routes. Topical application resulted in a higher C max and a 327% higher area under the curve (AUC) of N ‐acetyl‐AHT, indicating a first‐pass effect in the EpiDerm™ models. In accordance with in vivo observations, there was a concomitant decrease in the C max and AUC of AHT‐ O ‐sulphate after topical, compared with systemic application. A similar alteration in metabolite ratios was observed using a 24‐well full‐thickness skin model, EpiDermFT™, indicating that a first‐pass effect was also possible to detect in a more complex model. In addition, washing the EpiDermFT™ after 30 min, thus reflecting consumer use, decreased the systemic exposure to AHT and its metabolites. In conclusion, the skin–liver Chip2 model can be used to (a) recapitulate the first‐pass effect of the skin and alterations in the metabolite profile of AHT observed in vivo and (b) provide consumer‐relevant data regarding leave‐on/rinse‐off products. Abstract : The HUMIMIC EpiDerm™ and liver Chip2 microfluidic model was used to investigate the effect of consumer‐relevant application scenarios on the metabolic fate of 4‐amino‐2‐hydroxytoluene (AHT). The metabolic profile of 100‐μM AHT was the same after topical and systemic application, due to saturation of EpiDerm™ metabolising enzymes. However, the first‐pass effect of the skin (using epidermal and full‐thickness models) and the alteration of the metabolite profile of 2.5‐μM AHT mimicked the leave‐on/rinse‐off and route‐specific effects observed in vivo.